Characterization of globin genes in Atlantic cod - Katrín Halldórsdóttir 1972- (2007)
An understanding of biology of a wild species able to support a major fishery of great magnitude like the Atlantic cod Gadus morhua is important from both fisheries management as well as from a purely biological standpoint. The hemoglobin HbI locus shows effects of natural selection and adaptation to environmental conditions. Globin gene regions have been characterized in some fish species. All of them show linked α and β loci located on the same chromosome. I report here a characterization of linked β and α globin genes in Atlantic cod with proximal regulatory elements. The genes are oriented tail to head in a 5' to 3' direction. The orientation of globin genes in Atlantic cod thus differs from orientation in other fish species described so far. Applying a PCR based strategy for genomic exploration, I show that there are ten clusters of linked β/α globin genes in the genome of Atlantic cod which likely represent different β/α gene sets or different alleles at some loci. The results are based on cloned and sequenced contigs of approximately 3000 base pairs long fragment of the linked β/α gene sets. The different gene sets differ from each other by a number of nucleotides in linkage disequilibrium including non-synonymous differences. Skilningur á líffræði villtrar tegundar sem er undirstaða fiskveiða af þeirri stærðargráðu eins og þorskur, Gadus morhua, gerir, er mjög mikilvægur bæði fyrir stjórn fiskveiða sem og frá líffræðilegu sjónarhorni. Hemóglóbin lókusinn HbI sýnir áhrif náttúrulegs vals og aðlögun að umhverfisaðstæðum. Glóbin gena setum hefur verið lýst í nokkrum fiskategundum. Í þeim öllum eru α og β glóbin setin tengd saman á litningi. Ég lýsi hér samtengdum β og α glóbin genasetum í þorski ásamt nálægum stjórnröðum. Genin eru í sömu stefnu á litningnum, með β genið 5'. Afstaða genanna hvors til annars er í 5' til 3' stefnu („tail to head“ eða „rófa í haus“). Stefna β/α glóbin gena hvors til annars í þorski er því frábrugðin stefnu þeirra í þeim fisktegundum þar sem þessu hefur verið lýst. Með því að ...